Genome-wide DNA methylation in neonates exposed to maternal depression, anxiety, or SSRI medication during pregnancy - Non, Amy L; Binder, Alexandra M; Kubzansky, Laura D; Michels, Karin B (Epigenetics, 2014)
Despite the high prevalence of depression, anxiety, and use of antidepressant medications during pregnancy, there is much uncertainty around the impact of high levels of distress or antidepressant medications on the developing fetus. These intrauterine exposures may lead to epigenetic alterations to the DNA during this vulnerable time of fetal development, which may have important lifetime health consequences. In this study we investigated patterns of genome-wide DNA methylation using the Illumina Infinium Human Methylation450 BeadChip in the umbilical cord blood of neonates exposed to non-medicated maternal depression or anxiety (n = 13), or selective serotonin reuptake inhibitors (SSRIs) during pregnancy (n = 22), relative to unexposed neonates (n = 23). We identified 42 CpG sites with significantly different DNA methylation levels in neonates exposed to non-medicated depression or anxiety relative to controls. CpG site methylation was not significantly different in neonates exposed to SSRIs relative to the controls, after adjusting for multiple comparisons. In neonates exposed either to non-medicated maternal depression or SSRIs, the vast majority of CpG sites displayed lower DNA methylation relative to the controls, but differences were very small. A gene ontology analysis suggests significant clustering of the top genes associated with non-medicated maternal depression/anxiety, related to regulation of transcription, translation, and cell division processes (e.g., negative regulation of translation in response to oxidative stress, regulation of mRNA export from the nucleus, regulation of stem cell division). While the functional consequences of these findings are yet to be determined, these small DNA methylation differences may suggest a possible role for epigenetic processes in the development of neonates exposed to non-medicated maternal depression/anxiety.